Image of destruction. Vertigo aesthetics - Ramos Sánchez, Miguel Ángel (Estudios de Filosofía, 1997)
The traditional context for images has been discomposed because of the main technical stamp of nowadays culture. Images fali over us hastily, and as a consequence the eye works notas an organiser nor does the usual contemplative attitude. The eye sees no more; it just vibrates. Hence, the author propases an Aesthetics of Vertigo. lts purpose is to concíliate the traditional conception of images (which means today a defense of painting) and the vanishing character proper to the present images technical vertigo. This Aesthetics pleads for a reflexive faculty of judgement, able to face finiteness soberly and pragmatically.